Marking Sacred Time and Sacred Place in The Grave of Sunan Pandan Aran - Usman, Abraham (JURNAL PENELITIAN, 2018)
This study analyzes Islamic relations and traditions in the Pilgrimage ritual debate. The subject matter of the study emphasizes the aspects of timing and place of pilgrimage as important in the zairah procession. Through qualitative research, with the setting of the Tomb of Sunan Pandan Aran, data was obtained from interviews, observation and documentation. This study succeeded in revealing the grave pilgrimage debate in the contestation of traditional and modernist Islam. On the other hand, the community believes that the right time and day are important elements in the success of the pilgrimage. Making a pilgrimage in the middle of the night, especially on Tuesday and Friday nights becomes a determinant in the pilgrimage ritual. They feel fear, admiration, love, joy. These religious feelings are important things that make them miss, so they always want to come back again and again. The tomb of Sunan Pandan Aran is believed to be a holy place, the place of prayer for pilgrims is granted, and is considered sacred and mystical as a religious narrative of the community